A novel comparative pattern count analysis reveals a chronic ethanol-induced dynamic shift in immediate early NF-κB genome-wide promoter binding during liver regeneration12. Issue 3 (5th February 2016) - Kuttippurathu, Lakshmi; Patra, Biswanath; Hoek, Jan B.; Vadigepalli, Rajanikanth
Abstract : We demonstrate a novel methodology to identify key immediate early regulatory mechanisms during liver regeneration, which are altered by adaptation to ethanol intake. Abstract : Liver regeneration after partial hepatectomy is a clinically important process that is impaired by adaptation to chronic alcohol intake. We focused on the initial time points following partial hepatectomy (PHx) to analyze the genome-wide binding activity of NF-κB, a key immediate early regulator. We investigated the effect of chronic alcohol intake on immediate early NF-κB genome-wide localization, in the adapted state as well as in response to partial hepatectomy, using chromatin immunoprecipitation followed by promoter microarray analysis. We found many ethanol-specific NF-κB binding target promoters in the ethanol-adapted state, corresponding to the regulation of biosynthetic processes, oxidation–reduction and apoptosis. Partial hepatectomy induced a diet-independent shift in NF-κB binding loci relative to the transcription start sites. We employed a novel pattern count analysis to exhaustively enumerate and compare the number of promoters corresponding to the temporal binding patterns in ethanol and pair-fed control groups. The highest pattern count corresponded to promoters with NF-κB binding exclusively in the ethanol group at 1 h post PHx. This set was associated with the regulation of cell death, response to oxidative stress, histone modification, mitochondrial function, and metabolic processes. Integration with the global gene expression profiles to identify putative transcriptional consequences of NF-κB binding patterns revealed that several of ethanol-specific 1 h binding targets showed ethanol-specific differential expression through 6 h post PHx. Motif analysis yielded co-incident binding loci for STAT3, AP-1, CREB, C/EBP-β, PPAR-γ and C/EBP-α, likely participating in co-regulatory modules with NF-κB in shaping the immediate early response to PHx. We conclude that adaptation to chronic ethanol intake disrupts the NF-κB promoter binding landscape with consequences for the immediate early gene regulatory response to the acute challenge of PHx.